2020
DOI: 10.1038/s41598-020-72972-x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral effects induced by organic insecticides can be exploited for a sustainable control of the Orange Spiny Whitefly Aleurocanthus spiniferus

Abstract: The Orange Spiny Whitefly (OSW) Aleurocanthus spiniferus (Hemiptera: Aleyrodidae) represents a new serious threat to Citrus spp., grapevine and ornamental plants in the whole Mediterranean area. Such threat urgently calls for the development of a sustainable control strategy, including insecticides compatible with biological control, and applicable also in organic citrus farming that represent an essential part of Mediterranean agricultural economy. Therefore, we evaluated the toxicity and the effects on host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
(97 reference statements)
1
5
0
Order By: Relevance
“…In addition, Cacopsylla pyricola Foerster (Hemiptera: Psyllidae) showed shorter phloem ingestions on plants treated with deltamethrin 42 . Regarding pyrethrin, it was also observed that the effect of this pesticide was more evident during the first hours of the recordings (fast repellent effect); that is, insects exposed to pyrethrin exhibited a reduction in the number of Xc and Xi events and their duration during the first 2 h. A reduction in the probing frequency on plants treated with pyrethrin compared with the control was previously observed on Aleurocanthus spiniferus whiteflies 43 . Moreover, the antifeedant activity of pyrethrins was previously reported on other hemipterans, and this effect is known to decrease over time 44 .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In addition, Cacopsylla pyricola Foerster (Hemiptera: Psyllidae) showed shorter phloem ingestions on plants treated with deltamethrin 42 . Regarding pyrethrin, it was also observed that the effect of this pesticide was more evident during the first hours of the recordings (fast repellent effect); that is, insects exposed to pyrethrin exhibited a reduction in the number of Xc and Xi events and their duration during the first 2 h. A reduction in the probing frequency on plants treated with pyrethrin compared with the control was previously observed on Aleurocanthus spiniferus whiteflies 43 . Moreover, the antifeedant activity of pyrethrins was previously reported on other hemipterans, and this effect is known to decrease over time 44 .…”
Section: Discussionsupporting
confidence: 55%
“… 42 Regarding pyrethrin, it was also observed that the effect of this pesticide was more evident during the first hours of the recordings (fast repellent effect); that is, insects exposed to pyrethrin exhibited a reduction in the number of Xc and Xi events and their duration during the first 2 h. A reduction in the probing frequency on plants treated with pyrethrin compared with the control was previously observed on Aleurocanthus spiniferus whiteflies. 43 Moreover, the antifeedant activity of pyrethrins was previously reported on other hemipterans, and this effect is known to decrease over time. 44 Nevertheless, the impact of pyrethrin on P. spumarius feeding behaviour and its repellent effect tend to disappear in a few hours, possibly as a result of pyrethrin photolability.…”
Section: Discussionmentioning
confidence: 89%
“…It is therefore mandatory to rethink about X. fastidiosa control strategies, developing and applying long-term sustainable tools against vectors and safeguarding the ecosystem services. Manipulation of vector behaviors by confounding the cues used by the insect for host-plant recognition, or reducing host plant suitability and residency time, or interfering with insects' communication during crucial steps of their life cycle, could represent an efficient and environmentally-safe strategy for the containment of vector-borne plant pathogens (Fereres & Moreno 2009;Mazzoni et al 2009;Mokrane et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the serious damage caused by this pest, it has been reported as quarantine pest in many countries (EPPO A2 list 1 ). To date, there are limited studies on A. spiniferus that are mainly focused on population dynamics, insecticide selections, biological control and color plates ( Mokrane et al, 2020 ; Nugnes et al, 2020 ; Tian et al, 2020 ). In this study, we investigated the structure, distribution, and abundance of the antennal sensilla in the adult male and female A. spiniferus by scanning electron microscopy.…”
Section: Introductionmentioning
confidence: 99%